Multicast routing and allocation of wavelengths in a WDM network with splitters and converters. Issue 2 (3rd July 2021) - Dafeur, Abdelhakim; Cousin, Bernard; Ziani, Rezki
This paper deals with the problem of multicast routing and the allocation of wavelengths in a WDM network with optical splitters and converters. We present an exact formulation in integer linear programming (ILP) to find a set of optical structures connecting a source to a set of destination nodes. We use a new optical structure called hierarchical. The problem of multicast routing with sparse wavelength conversion and sparse splitting using the hierarchical structure has not yet been studied. So, our main contribution consists of introducing new optical constraints of wavelength converters with the hierarchical structure. The objective is to focus on the benefits and performances of using wavelength converters in a WDM network. Simulation results show that the hierarchical structure gets better results in terms of overall link cost and the number of wavelengths in the case of WDM network sparse wavelength converters than the WDM network without converters.